Pengaruh Work Engagement, Job Satisfaction, Workaholism dan Burnout Terhadap Turnover Intention pada Karyawan Generasi Milenial di Kabupaten Lamongan - Pamungkas, Muhammad Robah; Sulton, Muhammad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the effect of Employee well-being (Work Engagement, job satisfaction, burnout, and Workaholism) on Turnoverintention among millennial employees in Lamongan Regency. Data collection was conducted through a questionnaire filled out by 350 millennial respondents in Lamongan Regency. The analysis tool used was IBM SPSS version 29.0 for Windows. The results showed that Work Engagement (X1) had a negative but insignificant effect on Turnover Intention (Y), while Job Satisfaction (X2) had a negative and significant effect on Turnover Intention (Y). Meanwhile, Workaholism (X3) had a positive and significant effect on Turnover Intention (Y), and Burnout (X4) also had a positive and significant effect on Turnover Intention (Y). These findings highlight the importance of the role of managing Employee Well-Being which includes Work Engagement, job satisfaction, burnout, and Workaholism, because it can have an impact on Turnoverintention among the millennial generation in Lamongan Regency. The managerial implications of this study emphasize the importance of addressing aspects of employee well-being (Work Engagement, job satisfaction, burnout, and Workaholism) to mitigate problems related to Turnover Intention among the millennial generation in Lamongan Regency.